JONES, Bronwen M. A.; BALL, Stephen J. (org.). Neoliberalismo e educação. Tradução: Janete Bridon. Ponta Grossa: Editora UEPG, 2025. (Práxis Educativa, 2025)
Resenha: JONES, Bronwen M. A.; BALL, Stephen J. (org.). Neoliberalismo e educação. Tradução: Janete Bridon. Ponta Grossa: Editora UEPG, 2025.